Inhibitive Effects of FGF2/FGFR1 Pathway on Astrocyte-Mediated Inflammation in vivo and in vitro After Infrasound Exposure - Shi, Ya-Jun; Shi, Ming; Xiao, Li-Jun; Li, Li; Zou, Lin-Hui; Li, Chao-Yang; Zhang, Qin-Jun; Zhou, Lin-Fu; Ji, Xin-Chao; Huang, Huan; Xi, Ye; Liu, Ling; et al. (Frontiers in Neuroscience, 2018)
Infrasound, a kind of ambient noise, can cause severely disorders to various human organs, specially to central nervous system (CNS). Our previous studies have proved that infrasound-induced CNS injury was closely related with astrocytes activation and astrocytes-mediated neuroinflammation, but the underlying molecular mechanisms are still largely unclear. FGF2/FGFR1 (Fibroblast growth factor 2/Fibroblast growth factor receptor 1) pathway was reported to play an important role in anti-inflammation in CNS disorders. To further study the possible roles of FGF2/FGFR1 pathway in infrasound-induced CNS injury, here we exposed Sprague-Dawley rats or cultured astrocytes to 16Hz, 150dB infrasound, and explored the effects of FGF2 on infrasound-induced astrocytes activation and neuroinflammation. Western blotting, immunofluorescence and liquid chip method were used in this experiment. Our results showed that after 3-, or 7-day exposure (2h/day) of rats as well as 2h exposure of cultured astrocytes to 16Hz, 150dB infrasound, astrocyte-expressed FGFR1 was downregulated in vivo and in vitro. FGF2 pretreatment not only inhibited infrasound-induced astrocyte activation in rat hippocampal CA1 region, but also reduced the levels of pro-inflammatory cytokines, such as TNF-α, IL-1β, IL-18, IL-6 and IFN-γ in vitro and in vivo. However, FGF2 significantly upregulated the expression of FGFR1. Furthermore, we showed that FGF2 could attenuate IκBα phosphorylation, NF-κB p65 translocation, pro-inflammatory cytokines levels, and neuronal loss in the CA1 region induced by infrasound. On the contrary, PD173074, a special antagonist of FGFR1, could reverse the effects above in vitro and in vivo. Taken together, our findings showed that FGF2/FGFR1 pathway may exert inhibitive effects on astrocyte-mediated neuroinflammation in vitro and in vivo after infrasound exposure.